2005
DOI: 10.1074/jbc.m413065200
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Enhances the Sensitivity of Type I Protein Kinase A to cAMP

Abstract: The functional significance of the presence of two major (types I and II) isoforms of the cAMP-dependent protein kinase (PKA) is still enigmatic. The present study showed that peptide substrate enhanced the activation of PKA type I at low, physiologically relevant concentrations of cAMP through competitive displacement of the regulatory RI subunit. The effect was similar whether the substrate was a short peptide or the physiological 60-kDa protein tyrosine hydroxylase. In contrast, substrate failed to affect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 43 publications
2
46
0
Order By: Relevance
“…Binding of RI to the C subunits was reduced by ϳ50% upon treatment with 50 M forskolin and 500 M IBMX, which we used to get to a sustained increase of [cAMP] i , in agreement with previous results (Fig. 1 (35,36). In contrast, the PrKY/RI␤ interaction was not influenced by [cAMP] i (Fig.…”
Section: Inhibition Of Prkx and Orthologs By Human R Subunits-supporting
confidence: 79%
“…Binding of RI to the C subunits was reduced by ϳ50% upon treatment with 50 M forskolin and 500 M IBMX, which we used to get to a sustained increase of [cAMP] i , in agreement with previous results (Fig. 1 (35,36). In contrast, the PrKY/RI␤ interaction was not influenced by [cAMP] i (Fig.…”
Section: Inhibition Of Prkx and Orthologs By Human R Subunits-supporting
confidence: 79%
“…It has been demonstrated that both the mammalian type I␣ and the type II␤ holoenzymes are more stable in the presence of cAMP than thought previously and that the substrate can enhance the dissociation of PKA type I at low, physiologically relevant concentrations of cAMP but failed to affect the interaction of the subunits of type II kinase (26,27). In our laboratory, we have demonstrated the participation of the peptide substrate in the activation of a fungal (Mucor rouxii) holoenzyme by cAMP (29).…”
Section: Discussionmentioning
confidence: 65%
“…It has been demonstrated recently that although the addition of a molar excess of cAMP to the type I␣ PKA holoenzyme causes partial dissociation, it is only upon addition of a PKA peptide substrate, together with cAMP that full dissociation occurs. The authors also demonstrate that substrate plays a differential role in the activation of type I versus type II holoenzymes, which could explain some important functional differences between PKA isoforms (27,28). We have shown, some years ago, that peptide substrates were involved in the activation of a fungal PKA by cAMP (29).…”
Section: Resultsmentioning
confidence: 99%
“…PKAII is half-maximally activated at ~500 nM cAMP (Dostmann and Taylor, 1991;Viste et al, 2005), and based on data in these publications a decrease in cAMP from ~660 to ~140 nM would reduce the activity of PKAII by 90%. PKAI activity would also decrease, although the extent of this decrease is unknown, as values for the cAMP concentrations that half-maximally activate PKAI vary from 70 to 500 nM depending on the type and concentration of the substrate (Viste et al, 2005).…”
Section: Measurement Of Camp Changes In Follicleenclosed Mouse Oocytesmentioning
confidence: 99%
“…However, the magnitude of these changes was difficult to interpret because the oocytes were removed from their follicles, which would decrease cAMP, and because phosphodiesterase inhibitors were present, which would increase cAMP. Thus, it is unknown whether the decreases in cAMP that were observed in response to LH receptor stimulation were sufficient to affect the activity of PKA, which requires cAMP in the range of 70-500 nM for half-maximal activity (Dostmann and Taylor, 1991;Viste et al, 2005). LHstimulated decreases in cGMP occur in oocytes and whole follicles from hamsters (Hubbard, 1986), but whether the magnitude of these changes is physiologically significant and whether these decreases occur in other species are unknown.…”
Section: Introductionmentioning
confidence: 99%